THE EFFECT OF FASTING ON HEALTH OF DIGESTION SYSTEM - Munaya Fauziah; Dewi Purnamawati; Nurmalia Lusida; Irna Hasanah; Mahmudin Sudin (Fakultas Kesehatan Masyarakat Universitas Muhamamdiyah Jakarta, 2021)
The human body has important digestive organs such as the stomach. One of the gastric diseases, namely gastritis or ulcer, has started to be experienced due to a lack of knowledge about the factors that cause gastritis and the behavior to prevent gastritis. Gastritis, known as ulcer disease, is an inflammation or bleeding of the gastric mucosa caused by irritation, infection, and irregularity in eating patterns. The method used is a literature review article or literature review by examining 7 journals published from 2010-2020 regarding the effect of fasting on the health of the gastric digestive system which was carried out in April 2020. The results showed that there was a change in diet when fasting caused various changes in the body, especially in the digestive tract. Fasting gives the digestive system time to rest, which can reduce the risk or cure digestive health problems. The conclusion is that there is a relationship between diet, knowledge, and stress on the incidence of gastritis. Meanwhile, coffee consumption behavior and gender have no relationship with the incidence of gastritis.